Compounded pelleted fibre feed and hay pellets as substitutes for hay in horse feeding - Saastamoinen, Markku; Manninen, Merja; Rantanen, Asko (Agricultural and Food Science, 1992)
Use of compounded pelleted fibre feed and ground pelleted hay as substitutes for hay in horse feeding was investigated. Thirty horses were divided into a control group and two experimental groups. The control horses received 6 kg hay per day. The horses in the two experimental groups were fed 3 kg hay per day and the remainder of their hay portion was substituted with a compounded pelleted fibre-rich feed or pelleted hay. The influence of the diet on health, haemoglobin (Hb) and haematocrit (He) values, blood serum glucose concentration, as well as on faecal microflora and weight change was investigated. The health of the horses was found to be good, and the influence of the diets on the Hb and He values and faecal microflora as well as on weight change was not statistically significant. Horses receiving compounded feed had a higher (p<0.05) mean blood glucose concentration than the other horses due to the molasses used as an ingredient (25 %) of the compounded feed. Compounded pelleted fibre-rich feed as well as pelleted hay, both made of ground raw materials, were found suitable substitutes for hay in the diet of horses.